Impact of Socioeconomic Status on Paranasal Sinus Cancer Disease-Specific and Conditional Survival. (June 2022) - Sharma, Rahul K.; Del Signore, Anthony; Govindaraj, Satish; Iloreta, Alfred; Overdevest, Jonathan B.; Gudis, David A.
Objective: Socioeconomic status (SES) is often used to quantify social determinants of health. This study uses the National Cancer Institute SES index to examine the effect of SES on disease-specific survival and 5-year conditional disease-specific survival (CDSS; the change in life expectancy with increasing survivorship) in paranasal sinus cancer Study Design: Cross-sectional analysis. Setting: National Cancer Institute's Surveillance, Epidemiology and End Results (SEER) program. Methods: A study of adults with sinus cancer between 1973 and 2015 was performed. The Yost index, a census tract–level composite score of SES, was used to categorize patients. Kaplan-Meier analysis and Cox regression for disease-specific survival were stratified by SES. CDSS was calculated with simplified models. Logistic regression was conducted to identify risk factors for advanced stage at diagnosis, multimodal therapy, and diagnosis of squamous cell carcinoma. Results: There were 3437 patients analyzed. In Cox models adjusting for patient-specific factors, the lowest SES tertile exhibited worse mortality (hazard ratio, 1.22; 95% CI, 1.07-1.39; P < .01). After addition of treatment and pathology, SES was not significant ( P = .07). The lowest SES tertile was more often diagnosed at later stages (odds ratio [OR], 1.52; 95% CI, 1.12-2.06; P < .01). For those with regional/distant disease, the middle tertile (OR, 0.75; 95% CI, 0.63-0.90; P < .01) and lowest tertile (OR, 0.75; 95% CI, 0.62-0.91; P < .01) were less likely to receive multimodal therapy. SES tertiles primarily affected 5-year CDSS for regional/distant disease. CDSS for all stages converged over time. Conclusion: Lower SES is associated with worse outcomes in paranasal sinus cancer. Research should be devoted toward understanding factors that contribute to such disparities, including tumor pathology and treatment course.